ACCUMULATION OF NUTRIENTS AND DRY MATTER PRODUCED BY Crotalaria juncea CULTIVED IN CERRADO - Silva, M. S.; Oliveira, G. R. F.; Merloti, L. F.; Sá, M. E. (Revista Brasileira de Engenharia de Biossistemas, 2017)
The green manuring with Crotalaria juncea is a strategy widely used in the Cerrado to improve the chemical, physical and biological characteristics of the soil, in a matrix that presents natural limitations to the proper performance of the crops. The objective of this work was to verify the accumulation of nutrients and dry matter production by C. juncea cultivated in Cerrado soil. Two experiments were carried out in the years 2015 and 2016, in a dystrophic Red Latosol, in the city of Selvíria, MS, Brazil. Seeds were insered in an area with conventional preparation, without the use of fertilization. At 80 days after sowing and before blooming, the plants were managed mechanically. The following evaluations were performed: (a) Dry matter production: the samples obtained from the plants were desiccated and the average dry matter yield was extrapolated to a unit of kg ha-1. (b) Accumulation of nutrients: after collecting plant samples, the macronutrients and micronutrients contents were determined and, posteriorly, the content of each nutrient was multiplied by the dry mass of C. juncea produced, obtaining the accumulation of macronutrients (g kg-1) and micronutrients (mg kg-1). The green manure presented high dry matter production and excellent accumulation of nitrogen, potassium and iron.